ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING MANAGEMENT IN THE FORMATION OF STUDENT CHARACTERS AT STATE SENIOR HIGH SCHOOL I OF PANYABUNGAN - Siti Hawa Lubis (State Islamic University of North Sumatra Indonesia, 2018)
The study aims to find out more about the effect of teaching Islamic Education (PAI) subjects on the character building for students of State Senior High School I of Panyabungan. This research was carried out with a qualitative approach. The data in this study were obtained by conducting direct interviews with school stakeholders including principals, teachers, counselors and others. The results of this study are; through Islamic Education Teaching Material Teaching (PAI), State Senior High School I of Panyabungan has succeeded in shaping the character of students which include; behave well, honest, virtuous, responsible, trustworthy, carrying out discipline and always on time. As a conclusion, Islamic Religious Education (PAI) became one of the important material to be taught in public high schools in particular and all high schools in general. Because Senior High Schools are still very minimal knowledge of religion as a foundation for the formation of student character. Keywords; Islamic Religious Education (PAI) Learning, Management of PAI Learning, Student Character Formation